Сomposition and structure features of the Vikulov productive deposits (Krasnoleninsky arch) and their influence on reservoir properties - N. I. Korobova; N. S. Shevchuk; E. E. Karnyushina; R. S. Sautkin; E. A. Krasnova (Georesursy)
Both sedimentological factors and secondary processes of lithogenesis influenced the formation of porosity and permeability properties of the reservoir rocks of the Vikulov suite of the Krasnoleninskoe field. The former includes the conditions of sedimentation of the deposits of the Vikulov suite, which at the initial stages of its formation were controlled by the development of a system of incised river valleys, the stages of filling of which, like their composition, have their own characteristics. Also, various genetic types of deposits were formed here. The formation of the upper part of the Vikulov suite took place in a shallow-marine setting, in conditions of storm and wave shallow water, which affected the thin-layered structure of the VK1-3 reservoir. On the other hand, in the sections of a number of wells, dense interlayers are noted, the formation of which is associated with both sedimentation and superimposed processes in lithogenesis, including the formation of hydrocarbon deposits. Therefore, the prediction of the distribution of productive reservoir rocks is the main task when creating a petrophysical model of the field, and to solve this problem, the methods of lithofacies and staged core analysis are used in the work.